A comprehensive review of carbon sequestration and its assessment techniques using remote sensing and geospatial methods - Imen Ben Salem (Environmental Research Communications)
Global warming has elevated carbon sequestration as a critical strategy for mitigating climate change, while enhancing sustainability in productivity. Agricultural land use systems contribute substantially to CO _2 emissions due to crop residues, shifting cultivation practices, low-biomass crops, land degradation, and deforestation. The significant rise in CO _2 emissions over the past thirty years is associated with burning fossil fuels, leading to substantial environmental changes, including global warming. Remote sensing (RS) and Geographic Information Systems (GIS) are advanced geospatial technologies that facilitate the rapid evaluation of terrestrial carbon stock over extensive regions. An integrated RS-GIS approach for carbon stock estimation and precision carbon management is a time and cost-effective strategy for implementing appropriate management at local and regional scales. The paper reviews various remote sensing (RS) methodologies for evaluating carbon sequestration (CS), focusing on various land ecosystems associated with vegetative indices and biomass that address carbon stocking. It explores associated challenges, opportunities, and emerging trends, examining conventional and RS techniques while highlighting their limitations and current and developing methodologies while identifying the key RS variables essential for representing predictors of carbon sequestration. This also highlights the importance of geospatial tools in evaluating different community services. The paper evaluates several approaches and sensors, such as optical, RADAR, and LiDAR-based RS, commonly used for biomass estimation and CS assessment. The paper concludes by emphasizing the need for further research to bridge gaps and address challenges in implementing these new strategies for precision carbon management. Overall, geospatial technologies are valuable tools for accurate carbon sequestration estimation, particularly in remote and challenging terrains, and benefit the research communities focused on the carbon cycle, remote sensing, climate change elucidation, and global climate changes.